Zimevit: un biofungicida que combina la acción de una bacteria y una levadura para el control del moho gris de la vid ocasionado por Botrytis cinerea. (Revista Brasileira de Agroecologia, 2012)
Botrytis cinerea, causes significant losses in grapes production. Zimevit, a biological product developed in Uruguay that combines the action of a bacterium (Bacillus subtilis, UYBC38) and the yeast (Metschnikowia pulcherrima, M26), was tested in field in the varieties Cabernet Franc and Gewurztraminer. The treatments were: Zimevit, iprodione as conventional treatment, and water as untreated control. In the three tests carried, Zimevit application resulted in a lower incidence and severity of gray mold on grapes at harvest. No statistically significant differences were observed between the Zimevit and iprodione treatments. The decrease in the incidence and severity would indicate that Zimevit has a double inhibitory effect on B. cinerea, both on spores germination and disease development. This effect is attributed to thecombined action of M. pulcherrima and B. subtilis. In spite of that further evaluations are needed in years with favorable conditions to disease development, Zimevit appears as a tool with potential for use inintegrated management systems of gray mold of grapes in Uruguay.